If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + ywhenx = 3 Reorder the terms: ehnwxy + x = 3 Solving ehnwxy + x = 3 Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '-1x' to each side of the equation. ehnwxy + x + -1x = 3 + -1x Combine like terms: x + -1x = 0 ehnwxy + 0 = 3 + -1x ehnwxy = 3 + -1x Divide each side by 'hnwxy'. e = 3h-1n-1w-1x-1y-1 + -1h-1n-1w-1y-1 Simplifying e = 3h-1n-1w-1x-1y-1 + -1h-1n-1w-1y-1
| 1. 6x+10=6x+94 | | (b^7)^2/7 | | 3m+6=6m-3 | | -67=-(j-(-22)) | | 4(2+7x)=204 | | D=1/2mq | | 1. 4(2+7x)=204 | | -5(x-10)=-36 | | K-3/4=4 | | 1/6k=-2/3 | | 4v+12=56 | | X=-9+3y | | -4(-9+6x)=84 | | 6y+6=8y-16 | | y+8=2(4x+4) | | 5n+34=-4(1-7n) | | 24+4=16 | | -6x+12y=-6 | | 7-18=-116 | | 15x-10+5x+5=95 | | 3/4s=5/4 | | (7x+2)(4x+1)(1x-5)=0 | | 2/3(9x-12)=4x=6 | | 6p+5=77 | | 16x+6=360 | | 96y-154=-43y+263 | | 3/4s=2/3 | | t^2-14*t+40=0 | | 4x^3+16x^2+8x-448=0 | | 3(u+1)+2u=5(u+1)+5 | | 8z-6=24 | | .7n-4=0 |